Development of Science Literacy-Based IPAS Teaching Materials to Improve the Character of Environmental Care of Grade IV Elementary School Students - Nanang Farid; Rasiman Rasiman; Bagus Ardi Saputro (Dinasti Publisher, 2025)
This research aims to describe validity, practicality, and effectiveness Science literacy-based teaching materials can improve the character of caring for the environment in grade IV elementary school students. This study uses the Research and Development (R&D) held at SD Negeri Blado 03 Blado District, Batang Regency in the 2024-2025 school year A total of 24 children. The test instruments used are Authentic assessment tests, validation sheets and teacher and student response questionnaires. The normality test and the homogenity test were used for the test question test. Data analysis used t-test and N-Gain. Based on the results of the study, it can be concluded as follows: (1) Validation of science literacy-based science literacy teaching materials to Improve the Character of environmental care in grade IV elementary school students including aspects of materials, media, and science questions about the Impact of Human Activities on the Environment at an average level of 90.85% in the very valid category, (2) The practicality of science literacy-based teaching materials to Improve the character of environmental care in grade IV elementary school students including the perception of teachers and participants educated at an average level of 86.14% in the very practical category, (3) Effectiveness of Teaching Materials (1) based on the results of the N Gain test proves that the IPAS score on the Impact of Human Activities on the Environment was obtained with an average gain increase of 0.61 (61%), in the category of quite effective, namely the interval value of 56 – 75; (2) based on Test Indipendent Sample test resulting in a calculated t value of 13,280 > t table (2,024) means that there is a significant difference in the IPAS test score on the Impact of Human Activities on the Environment using science literacy-based IPAS teaching materials to Improve the Character of Environmental Care in Grade IV Elementary School students before and after Treatment.